Heterogeneous Colistin-Resistance Phenotypes Coexisting in Stenotrophomonas maltophilia Isolates Influence Colistin Susceptibility Testing - Martínez-Servat, Sònia; Yero, Daniel; Huedo, Pol; Marquez, Roser; Molina, Gara; Daura, Xavier; Gibert, Isidre (Frontiers in Microbiology, 2018)
The polymyxin antibiotic colistin shows in vitro activity against Stenotrophomonas maltophilia. However, an increased incidence of colistin-resistant isolates has been recently observed. In addition, in vitro evaluation of colistin susceptibility for this organism has been problematic. The aims of this study were to investigate the colistin-resistance phenotypes displayed by S. maltophilia and their potential association with the challenging determination of colistin susceptibilities for this organism by even the recommended method. Colistin-resistance phenotypes were inferred by use of the recommended broth microdilution method in different clinical isolates of S. maltophilia. Most of the strains showed non-interpretable MICs for colistin due to an incomplete growth inhibition in wells of the microdilution plate. In addition, the subpopulation of bacteria resistant to colistin showed an increased ability to form biofilms on the plastic surface of MIC plates. The observed incomplete growth inhibition in the microdilution plates is compatible with a progressive adaptation to colistin or a heterogeneous susceptibility to this antibiotic. Therefore, to determine the existence of heteroresistance or adaptive resistance, four colistin-resistant clinical isolates were subjected to serial Etest assays, growth rate analyses, and the population analysis profile test. The experiments indicated that these S. maltophilia isolates display a colistin-resistant sub-population that survives and multiplies in the presence of the antibiotic. Interestingly, this phenomenon might not be explainable by the natural background mutation rate alone since the development of a resistant sub-population occurred upon the contact with the antibiotic and it was reversible. This complex colistin-resistance phenotype is exhibited differently by the different isolates and significantly affected colistin susceptibility testing. Furthermore, it can coexist with adaptive resistance to colistin as response to pre-incubation with sub-inhibitory concentrations of the antibiotic. Overall, the combined action of heterogeneous colistin-resistance mechanisms in S. maltophilia isolates, including colistin-induced biofilm formation, may hamper the correct interpretation of colistin susceptibility tests, thus having potentially serious implications on antimicrobial-therapy decision making.